HARMONIZATION OF LEGISLATION: LINGUISTIC-LEGAL ASPECT - Zhubaniyasova Салтанат Хамзакызы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
This article is devoted to the linguistic-legal aspects of harmonization of national legislation in the light of new criminal legislation of the Republic Kazakhstan. Great attention is paid to the questions of similarity of the use of branch terms and their appropriation to the requirements demanded to the terminology if this kind.